2004
DOI: 10.1258/0022215042790619
|View full text |Cite
|
Sign up to set email alerts
|

Secondary post-tonsillectomy haemorrhage and informed consent

Abstract: This is a prospective incidence study of 250 secondary post-tonsillectomy haemorrhages from a population of 2706 tonsillectomies performed over a seven-year period, which aims to ascertain the incidence and character of post-tonsillectomy secondary haemorrhage. Out of 250 post-tonsillectomy secondary bleeds (9.2 per cent of total; 95 per cent CI = 8.2 per cent - 10.4 per cent), 39 patients had a severe bleed (1.4 per cent; 95 per cent CI = 1.2 per cent - 2.1 per cent). The incidence of secondary tonsillectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 14 publications
5
33
1
1
Order By: Relevance
“…Our 0.6% RTT rate for primary haemorrhage is therefore comparable to the result found in the NPTA. Although our 1.1% secondary RTT haemorrhage rate is higher than the NPTA, it is still comparable to other published studies [6,7]. Our RTT rate for secondary haemorrhage could be explained by our low threshold for taking patients back to theatre for haemorrhage control compared to other centres, or it could be a reXection of the higher number of patients re-admitted with secondary haemorrhage.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our 0.6% RTT rate for primary haemorrhage is therefore comparable to the result found in the NPTA. Although our 1.1% secondary RTT haemorrhage rate is higher than the NPTA, it is still comparable to other published studies [6,7]. Our RTT rate for secondary haemorrhage could be explained by our low threshold for taking patients back to theatre for haemorrhage control compared to other centres, or it could be a reXection of the higher number of patients re-admitted with secondary haemorrhage.…”
Section: Discussionsupporting
confidence: 73%
“…Many studies have shown that secondary haemorrhage can occur between 24 h and 28 days post-operation, but generally tends to present in the Wrst week following surgery [6,8], and signiWcant bleeding which would require surgical arrest is rare after 10 days post-operation [9,10]. In our study, 65% (17/26) of the secondary haemorrhage cases required RTT in the Wrst postoperative week, seven of these cases (41%) were presented on the seventh post-operative day.…”
Section: Discussionmentioning
confidence: 99%
“…If only active bleeds were counted, the PTH rate was less than half (3.4%). A British study of secondary PTH distinguished between 'severe bleeding', which required blood transfusion or RTT, and 'nonsevere' bleeds [8] . They reported a 9% overall risk of bleeding, but only a 1.4% risk of severe bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Seconder tonsil haemorrhages tend to occur in the first week after surgery (5,28) and rarely require surgery after the first 10 days (29,30). When the patient data in the study were examined, it was observed that the hemorrhage occurred mainly between postoperative 6th and 10th days and there was no hemorrhage requiring surgery after the 13th day of surgery.…”
Section: Discussionmentioning
confidence: 99%